TRANSLOKASI SARANG PENYU SISIK (Eretmochelys imbricata) SEBAGAI UPAYA PERLINDUNGAN EKOSISTEM LAUT DI TAMAN NASIONAL KEPULAUAN SERIBU - Tegas Gentur Sosiawan; Tatang Mitra Setia (UIN Sunan Gunung Djati Bandung, 2023)
Turtle is one of the biodiversity found in the thousand islands whose existence needs to be maintained because it has a vital role in maintaining the marine ecosystem balance. Apart from being a conservation area, the Thousand Islands is a strategic area for national tourism. Tourism activities will indirectly affect the environmental conditions of the turtle habitat. In this study, we want to know the number of turtle eggs collected during 2018-2021, the distribution of spawning locations, and the percentage rate of hatching success. The method used is descriptive quantitative. The data studied are related to the number of turtle eggs that have survived, the location of the discovery of turtle nests, and the month of discovery obtained from reports on monitoring activities of wild plants and animals at the Thousand Islands National Park Center. This data calculates the percentage of hatching success of semi-natural turtle hatching in three locations. Based on the data, 21 islands have been identified as nesting sites for turtles over the last four years. The turtle nesting locations were found on six islands in the core zone. The rest are in the tourism use zone, and one of them is on a residential island. Based on the study results, the island which is the nesting location for turtles is an island with relatively flat topography, tends to be quiet from human disturbances, is small in size with medium vegetation density, and has a reasonably vast coastline. The percentage of successful semi-natural turtle eggs hatching in the Thousand Islands National Park for the last four years is 69.8%. It is still inadequate, so it is necessary to evaluate the management of the translocation of the hawksbill nest (Eretmochelys imbricata) activity.